O movimento de Jesus e a doutrina dos apóstolos - Paim, Noêmia da Silva Veloso (2015)
This research seeks to identify if the doctrine of the apostles mentioned in Acts 2:47 reflects the teachings received by the apostles from the Jesus Movement, in the light of the canonical and extra canonical context of the Old Testament, Intertestamental and New Testament periods, and if these teachings reflected the formative process of the teachings left by Jesus during the three and a half year period of terrestrial life of the Master, resulting in Christianity. The first part reveals how God communicates with his people. For this, the figure of the prophet comes into play, which will discourse in favor of a re-approximation of the people with the God of the covenant. The promise given is in the sense of restoring the communion if the worship practices of Israel s neighboring nations are abandoned. The trilogy punishment-repentance-forgiveness is announced as a condition for the restauration of the nation assailed by invaders. The second part shows how, upon their being uprooted from the land, the Israelites come to yearn for the restauration of the kingdom of Israel and how the return from the exile is marked by the hope for a new beginning, in which the promises announced by the prophets would be fulfilled and how the Lord of Hosts would once again fight for his people, having at the fore a Liberator in the patterns of Moses. It shows how the Messiah is anxiously awaited and how the Roman yoke exacerbates the nationalist tempers. It is in this context that the figure of Jesus emerges in Palestine in the midst of a cultural mix and various religious segments which had their own interpretation of the Jewish Scriptures. The Jesus Movement is birthed in Galilee and after the death of its leader, its followers receive the task of continuing the mobilization in favor of the implantation of the Kingdom of God, and it is no longer directed only toward the nationals of Israel but to all peoples and all nations. The third and last part reveals how the followers of Jesus carried on his proposals: how they established themselves, how they organized themselves and how they propagated the legacy of Jesus. It also reveals the characters which stood out after the ascension of Jesus and the role of each one in the propagation of the Gospel and in the consolidation of Christianity, the structure that followed the Jesus Movement.